PENGARUH JENIS DAN KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) VARIETAS TOSAKAN - Gerald Sehat Manullang, Abdul Rahmi dan Puji Astuti (Universitas 17 Agustus 1945 Samarinda, 2014)
Objectives of the research were to study the effect of type and concentration organic liquid fertilizer, as well as their interaction on the growth and yield of mustard green; and to find proper type and consentration of organic liquid fertilizer for better growth and production of mustard green. The research was carried out from September to October 2012, since preparation of growing media until crop harvested. It was held at Experiment Garden Area of Faculty of Agriculture, The 17th ofAugust 1945 University, Samarinda. The research employed Completely Randomised Design (CRD) with factorial 2 x 5 experiment and 3 replications. The first factor was type of organic liquid fertilizer (B), that consisted of two levels, namely: Nasa (b1), and Bio Sugih (b2). The second factor was concentration of organic liquid fertilizer (N), that consisted of five levels, namely: no organic liquid fertilizer as control (n0); 1,0 ml l-1 water (n1); 2,0 ml l-1 water (n2); 3,0 ml l-1 water (n3), and 4,0 ml l-1 water (n4). Results of the research indicated that: (1) organic liquid fertilizer types (B) affect significantly on plant weight, but it did not affect significantly on plant height and number of leafs at 7 and 21 days after planting and at harvest time; (2) concentration of organic liquid fertilizer (N) affect significantly on plant height at 21 days after planting and plant height at harvest time, number of leafs at 21 days after planting and plant weight, but it did not significantly on plant height at 7 days after planting and number of leaf at 7 days after planting and at harvest time. The highest plant weight was attained on the 2,0 ml l-1 water treatment (n2) with 185,59 g plant-1 while the worst one was on the no organic liquid fertilizer treatment (n0) with 84,02 g plant-1; and (3) the interaction between those two factors did not affect significantly on all parameters observed.